Tafsir Hak Asasi Manusia dalam Putusan Mahkamah Konstitusi Tentang Politik Dinasti Perspektif Fiqh Siyasah - Lailatul Fitria; Muhammad Faisol; Badrut Tamam (Rechtenstudent, 2022)
Dynastic politics is defined as leadership that only relies on the hands of groups that still have blood ties or kinship. In the Constitutional Court Decision Number 33/PUU-XIII/2015 concerning arrangements related to dynastic politics after a judicial review was carried out by parties who have legal standing and considered the law related to the prohibition of dynastic politics to be contrary to the 1945 Constitution. Because it was considered to formulate new norms and there was a violation of constitutional rights citizens to get equal opportunities in government. The interpretation of human rights following the issuance of the Constitutional Court decision No. 33/PUU-XIII/2015 concerning dynastic politics is that every citizen has the right to be elected and elected in regional head elections, so there is no longer any prohibition for incumbents to participate. in politics. Interpretation of Human Rights in the Constitutional Court Decision No. 33/PUU-XIII/2015 regarding dynastic politics if seen and understood more deeply from the point of view of fiqh principles based on the Constitutional Court's decision, regarding human rights, especially members of the incumbent' family to nominate regional heads, looking at so many data and surveys that show the negative impact of this dynastic politics, one of which often occurs is corruption, so based on fiqh principles it provides recognition that public interests must take precedence over special interests.